Larval Cytotoxic and Subacute Toxicity of Gardenia ternifolia, Rourea coccinea, and Cassytha filiformis Used in Traditional Medicine of Benin (West Africa) - E. Agbodjento; J. R. Klotoé; T. I. Sacramento; T. V. Dougnon; E. Déguenon; J. Agbankpé; K. Fabiyi; P. Assogba; M.-P. Hounkanrin; R. Akotegnon; T. J. Dougnon; J.-M. Atègbo (Journal of Toxicology)
The use of medicinal plants in traditional medicine is a common practice in developing countries. However, this unregulated or irrational use may pose a risk of toxicity to humans in the short and/or long term. Recent studies reported interesting ethnopharmacological, antioxidant, and phytochemical data on some medicinal plants used in the traditional treatment of male infertility in Benin. Unfortunately, very little data exist on the long-repeated dose toxicity of these medicinal plants. This study was aimed at evaluating the larval cytotoxicity and subacute toxicity of the hydroethanolic extract of Cassytha filiformis whole plant, Gardenia ternifolia roots, and Rourea coccinea leaves. The subacute toxicity of these plants was evaluated in male Wistar albino rats at three different doses (200, 400, and 800 mg/kg) according to the OECD 407 guidelines. Hematological and biochemical examinations and the histological study of the liver and kidneys were carried out. Larval cytotoxicity was assessed by the sensitivity of Artemia salina larvae to different concentrations of the studied plants extracts. The mean lethal concentration (LC50) was determined by the probit method. Subacute toxicity data indicated that there was no mortality or structural alterations of the liver and kidneys in the lot of treated animals. However, significant alterations in certain hematological and biochemical parameters (hematocrit, ASAT, and uremia) were noted. These abnormalities were observed in the lot of rats treated with Rourea coccinea and Cassytha filiformis extracts. Larval cytotoxicity data indicate that the studied plants extracts are not cytotoxic (LC50 > 0.1 mg/mL). These data suggest that the use in traditional medicine of studied plants at high doses and repeated over a long period of time requires special attention.